Enabling and empowering women in leadership in South African universities – Assessing needs and designing a response. (July 2021) - Seale, Oliver; Fish, Patrick; Schreiber, Birgit
Gender equity and women's access to senior leadership and management positions in universities are a major challenge not only in South Africa but on the African continent, too. For women to take up senior leadership roles more potently, it is essential that they not only cope with and compete in patriarchal systems but more so, are equipped to change patriarchal hegemony and shift the management discourse and culture to a pluralistic leadership culture where transformational leadership becomes the norm and praxis. This paper examines a needs analysis for leadership and professional development competencies of women in senior leadership positions in South African higher education and presents the discussion on these findings, based on the data collected from 74 participants. The conclusion reveals the participants' enthusiasm for personal leadership development as well as their readiness for impacting their leadership contexts. These findings, in turn, shape the content development of the Women in Leadership programme, designed by Higher Education Leadership and Management under the auspices of Universities South Africa.